Will terrorism end? - Ross, Jeffrey Ian (The roots of terrorism., 2006)
The September 11, 2001 terrorist attacks on the United States brought the issue of terrorism to the forefront of American attention and controversy. To determine how to prevent further destruction, it is necessary to understand the shadowy phenomenon that causes it. Who are the terrorists? What are their motives? What are the roots of this form of violence, and will it come to an end? What exactly is terrorism?